Trypanosoma brucei mitochondria contain RNA helicase activity. - Missel, A (1994)
Mitochondrial gene expression in kinetoplastid organisms such as Trypanosoma, Leishmania and Crithidia requires a posttranscriptional RNA processing event known as kRNA editing. During editing, uridine nucleotides get inserted and deleted into pre-mRNAs directed by small, metabolically stable RNAs, termed guide RNAs. Although the precise mechanism of the reaction is not understood, the accepted working model describes the formation of extended anti-parallel RNA helices between gRNA molecules with pre- and partially edited mRNAs as intermediates. These duplex structures must be separated to ensure the sequential action of multiple gRNAs in a 3' to 5' polarity on the mRNA molecule. In spite of this fact, no unwinding activity has heretofore been identified in kinetoplastid mitochondria. We report the characterisation of a RNA helicase activity within Trypanosoma brucei mitochondrial extracts. The activity unwinds 25- and 48 bp, tailed RNA duplex structures but fails to separate DNA strands. It can be destroyed by heat denaturation as well as by proteinase K treatment. The activity requires magnesium cations and acts in a NTP/dNTP dependent manner. Hydrolysis of a nucleoside triphosphate is required rather than mere NTP binding as deduced from a comparison of unwinding in the presence of ATP and AMP-PCP. RNA duplexes mimicking presumed kRNA editing intermediates are substrates of the unwinding activity and therefore, we address the possible involvement of a RNA helicase activity during kRNA editing.